2015
DOI: 10.1063/1.4927503
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio design of CsSn(XxY 1−x)3 (X and Y = Cl, Br, and I) perovskites for photovoltaics

Abstract: Ab initio calculations on CsSnX3 perovskites and mixed halides CsSn(XxY 1−x)3, X and Y = I, Cl, and Br, show that all of them have a direct band gap of ∼1 eV which can be tuned by varying the compositions of X and Y. The optimized supercells are tetragonal, orthorhombic or monoclinic. The top of the valence band arises from hybridization of Sn 4s and halogen p valence orbitals while the bottom of the conduction band has predominantly Sn p character. Similar to organo-metallic lead halides this is expected to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Interestingly, there is a striking similarity of these features with the band structure of the organometallic [40] perovskites which have been found to be very good for solar cell applications and which are currently attracting wide attention due to their high efficiency. A similar behavior of the band structure has been found in inorganic [41] perovskites. Also one can see a large density of states near the VB maximum (VBM) and CB minimum (CBM) for these materials which resembles the properties of phosphorene and arsenene [13].…”
Section: Electronic Structure Of One Two and Three Layers Of Sns Ansupporting
confidence: 80%
“…Interestingly, there is a striking similarity of these features with the band structure of the organometallic [40] perovskites which have been found to be very good for solar cell applications and which are currently attracting wide attention due to their high efficiency. A similar behavior of the band structure has been found in inorganic [41] perovskites. Also one can see a large density of states near the VB maximum (VBM) and CB minimum (CBM) for these materials which resembles the properties of phosphorene and arsenene [13].…”
Section: Electronic Structure Of One Two and Three Layers Of Sns Ansupporting
confidence: 80%
“…By means of a simple cubic unit cell it would not be possible to address these three aspects. This term has been employed in previous theoretical studies. Therefore, the following compositions were chosen: Cs x MA 1– x PbI 3 , MA x FA 1– x Sn 0.50 Pb 0.50 I 3 , and MA x FA 1– x PbBr 2.50 I 0.50 , where x = 0.0, 0.25, 0.50, 0.75, and 1.00.…”
Section: Theoretical Approach and Computational Detailsmentioning
confidence: 99%
“…Compared with the longer Pb–X bond in lead perovskites, the shorter Sn–X bond means a relatively larger degree of orbital overlap, thus Sn 5s and X p have a stronger antibonding coupling, which leads to a narrower band gap. Previous studies have reported that Sn-based perovskites have a direct band gap ranging from 0.75 to 1.3 eV and higher charge mobility (10 2 –10 3 cm 2 /V·s) compared to the Pb-based perovskites (10–10 2 cm 2 /V·s), very suitable for photovoltaic applications. , However, to the best of our knowledge only a few studies reported Sn-based solar cell efficiency greater than 13%. Among them, Ning et al achieved the highest efficiency of 14.6% by controlling the crystal orientation, but it is still far behind the 25.6% efficiency record of Pb-based devices . The main reason for the lower efficiency is the poor film quality, because Sn 2+ is easily oxidized to Sn 4+ spontaneously.…”
Section: Advantages Of Metal Halide Semiconductorsmentioning
confidence: 99%